Dysfunctional Consumer Behavior: Proposition of a Measurement Scale - Marília Lara Marcondes Machado de Oliveira; Andres Rodriguez Veloso (BBR: Brazilian Business Review)
This study focuses on the development of a scale that can identify customers that are more prone to behave in a dysfunctional manner. Dysfunctional Consumer Behavior can negatively influence the organization profits, since this kind of consumer can generate monetary losses, such as fixing damaged pr operty. Several hypotheses are proposed based on consumer characteristics that could foster dysfunctional behavior. For this, we used an hybrid methodology, combining Churchill’s (1979) with C - OAR - SE (2002). In order to develop the scale, scenarios with dy sfunctional behaviors where constructed. Respondents were asked to rate the appropriateness of each behavior and answers a group of questions based on the hypothesis developed. The data was collected over the Internet (Amazon Turk) and the statistical meth ods used for the scale development were cluster and discriminant analysis. The results showed evidence that it is possible to distinguish consumers through a discriminant function using interpersonal influence, such as aggressiveness, self - exposure, moral flexibility and machiavellianism; and personality aspects, such as dissatisfaction and acceptance.